2021
DOI: 10.1038/s41586-021-03570-8
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 tissue atlases reveal SARS-CoV-2 pathology and cellular targets

Abstract: This is a PDF file of a peer-reviewed paper that has been accepted for publication. Although unedited, the content has been subjected to preliminary formatting. Nature is providing this early version of the typeset paper as a service to our authors and readers. The text and figures will undergo copyediting and a proof review before the paper is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers apply.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

60
684
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 652 publications
(790 citation statements)
references
References 60 publications
(74 reference statements)
60
684
0
5
Order By: Relevance
“…Investigations of SARS-CoV-2 organotropism, its duration in the target organs and the correlation with disease progression are pivotal for developing effective strategies for the containment of the pandemic. Some studies revealed SARS-CoV-2 distribution in human tissues and viral shedding in body fluids, 18,[35][36][37][38] but the translational significance remains unclear. Our pathological evidence of SARS-CoV-2 presence in late stage of critically ill patients with COVID-19 suggests that continued usage of antiviral therapy is indispensable throughout the disease course.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations of SARS-CoV-2 organotropism, its duration in the target organs and the correlation with disease progression are pivotal for developing effective strategies for the containment of the pandemic. Some studies revealed SARS-CoV-2 distribution in human tissues and viral shedding in body fluids, 18,[35][36][37][38] but the translational significance remains unclear. Our pathological evidence of SARS-CoV-2 presence in late stage of critically ill patients with COVID-19 suggests that continued usage of antiviral therapy is indispensable throughout the disease course.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that definitive detection of SARS-CoV-2 spike or nucleocapsid protein by immunohistochemical (IHC) staining should confirm in situ viral presence in the lungs and extrapulmonary organs, thereby establishing direct evidence of viral infection of target organs. [16][17][18][19] In this study, we profiled SARS-CoV-2 organotropism using 26 autopsy cases from four cohorts in Wuhan, China, and evaluated virus-associated organ injuries. We classified COVID-19 into two pathological subtypes as intrapulmonary infection and systemic infection respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Moreover, the tolerance of these patients to physical activity and quality of life in general decreases sharply. 5 Again, the risk of long-term physical, cognitive, and emotional complications, the so-called PICS syndrome (Post Intensive Care Syndrome, Post-Reanimation Syndrome), increases in severe and critical patients who stay in intensive care units (ICU) for a long time. 6 Major risk factors include cognitive impairment, acute brain dysfunction, hypoxia, and arterial hypotension.…”
mentioning
confidence: 99%
“…Similar to HIV-1, SARS-CoV-2 profoundly interacts and modifies the cellular physiology both on the transcriptional [169][170][171][172][173] and protein levels [128,170,174,175]. Host responses to SARS-CoV-2 vary substantially depending on viral load, infection stage, disease severity, body tissue, and cell type as well as age and sex of the host [172,176,177]. Coupled to the induction of an antiviral response, the expression of the SARS-CoV-2 receptor and interferon-responsive gene ACE2 is upregulated by the infected host cell in a viral load-dependent manner.…”
Section: Virus-host Interaction and Exploitation Of The Cellular Machinerymentioning
confidence: 99%